Study of soil - water infiltration characteristics of soil mixtures for structural cells - Ngoh, Jun Wei (2015)
The land scarcity in Singapore is a well-known issue. With increasing population, more and more infrastructures and residential areas have been developed to meet the needs of the citizens. In order to promote the idea of “city in the garden”, numerous trees have been planted in the city, however, in the vicinity of the infrastructures or roads. The sub-base soils underneath the pavements are highly compacted to meet the strength requirements. This condition caused the trees to have limited space to grow since highly compacted soils hinder the roots from growing into these soils. In order to resolve this issue, there is a need to make changes to the underground growing environment without compromising the ability of the soils to carry the applied load. Structural cells filled with soil mixtures were introduced to replace the highly compacted sub-base soils. Selected soil mixtures were carefully designed to provide a suitable medium for roots to grow inside the structural cell. In this project, one type of the selected soil mixtures was investigated and it was the mixture of coarse granite chips with topsoil (GC-TS). Laboratory tests were performed to obtain the basic soil properties and hydraulic properties of the soil mixture GC-TS. Infiltration column tests with various boundary conditions were also conducted to investigate the infiltration characteristics of the soil mixture by monitoring the pore-water pressure head, volumetric water content and discharge rate. The tests included upward saturation, rapid drawdown, first rainfall and second rainfall. Furthermore, the drainage of the first and second rainfalls was also monitored. One-dimensional numerical modelling was also conducted for the first and second rainfalls and the results were compared with the results from the laboratory infiltration column tests. Good drainage property and moisture retention ability were found in the infiltration column of the soil mixture GC-TS. The pore-water pressure head profiles and volumetric water content profiles of the infiltration column tests and numerical modelling for both the first and second rainfalls were generally having good agreement.